O08.2 Sexual behaviour, risk and sexually transmitted infections before and after the introduction of the PrEP impact trial. (14th July 2019) - Turner, Katy; Harryman, Lindsey; Speare, Nathan; Horner, Paddy; MacGregor, Louis; Horwood, Jeremy; Kesten, Jo; Gardiner, Rebecca; North, Paul; Muir, Peter; Vickerman, Peter; Gompels, Mark; et al.
Abstract : Background: There is currently considerable interest the complex relationship between PrEP and STI incidence. Our Challenges and Opportunities of PrEP (CHOP) study uses qualitative and quantitative methods to ascertain the changes in behaviour and STI rates in high risk men/transgender/nonbinary persons who have sex with men (MSM/TPSM) before and after commencement of the PrEP Impact trial ('Impact') in our clinic (01/12/2017). Methods: We performed retrospective data analysis of clinic and laboratory records for MSM/TPSM attendees who attended a British sexual health clinic in a large urban area between 01/12/2016 and 28/02/2019. We used logistic regression to compare STI diagnoses (chlamydia, gonorrhoea and syphilis at any site) and sexual risk score in two time periods (1: 01/12/2016 – 31/11/17 and 2: 01/12/2017 to 28/02/2019). Results: Of 72, 667 attendances, 10, 918 were MSM/TPSM and, excluding duplicate entries (164) and those who were already HIV positive (236), this left 3, 407 individuals with 10, 518 attendances: 4, 378 (period 1) and 6, 140 (period 2). Mean HIV acquisition risk score at first visit in period 1 was 5.8 and 5.4 in period 2. In period 1 at first visit 13.5% (266/1, 975) had one or more STI compared with 20.2% (289/1143) in period 2, a rise of 6.7%. Logistic regression showed OR1.6 (p<0.001, 95%CI 1.35–1.95). STI diagnoses for subsequent visits in period 1, 6.3% (151/2403) attendances had one or more STIs diagnosed, and in period 2 10.9% (513/4708). This is a rise of 4.6% (OR 1.8 (p<0.001 95%CI 1.51–2.20). Conclusion: Although risk score was similar during both time periods, STI rates were significantly higher both at first visit and at subsequent visits. The qualitative aspect of this study will explore whether this reflects attracting more high risk MSM/TPSM into the service or whether use of PrEP increases risk-taking behaviour. Disclosure: No significant relationships.